2010
DOI: 10.1149/1.3479192
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline TiO[sub 2] Anatase with a Large Proportion of Crystal Facets (001): Lithium Insertion Electrochemistry

Abstract: The electrochemical behavior of TiO2 anatase with a predominant (001) face (ANA001) was studied by cyclic voltammetry of Li insertion and chronoamperometry. Both voltammetric and chronoamperometric diffusion coefficients and rate constants proved the higher activity of ANA001 toward Li insertion compared to that of a reference anatase material (C240) with dominating (101) facets. The enhanced activity of the anatase (001) face for Li insertion stems from synergic contributions of a faster interfacial charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 30 publications
7
51
0
Order By: Relevance
“…The conclusion about flatband potential shift was later reproduced on polycrystalline electrodes [19]. Also, the improved Li insertion was subsequently confirmed on polycrystalline (001)-oriented nanosheets [20]. They were prepared hydrothermally in HF medium according to Yang et al [11], and the follow-up studies [14,15,[21][22][23] report on materials enriched up to 90 % with the (001) face.…”
Section: Introductionmentioning
confidence: 90%
“…The conclusion about flatband potential shift was later reproduced on polycrystalline electrodes [19]. Also, the improved Li insertion was subsequently confirmed on polycrystalline (001)-oriented nanosheets [20]. They were prepared hydrothermally in HF medium according to Yang et al [11], and the follow-up studies [14,15,[21][22][23] report on materials enriched up to 90 % with the (001) face.…”
Section: Introductionmentioning
confidence: 90%
“…The synthesis of anatase enriched with (0 0 1) facets [26] triggered deeper investigations of orientation-dependent effects in nanocrystalline anatase materials. They provided various inputs for photocatalysis [33][34][35], DSCs [36][37][38][39][40] and Li-ion batteries [31,41,42]. These results also activated theoretical studies to explain the observed differences between (1 0 1) and (0 0 1) facets [32,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 74%
“…The phase-pure anatase (0 0 1) was prepared following the standard synthetic protocol for the TiO 2 nanosheets [26,32,42]. In the actual synthesis, 1.2 mL of 48% hydrofluoric acid was added to 10 mL of titanium(IV) butoxide.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, anatase TiO 2 nanocrystals with {001} facets exposed have attracted great attention because of their superior physical and chemical properties [16,17]. In the synthesis procedure for TiO 2 -HS, we have introduced HF to control the exposed facets of anatase to obtain the active crystal facets.…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical studies have pointed out that due to the special crystal structure of anatase, Li þ insertion/extraction will be probably facilitated through the {001} facets. Anatase TiO 2 nanosheet with {001} facets exposed have been proved to be an ideal host structure for fast and efficient lithium insertion/extraction [16,17]. In order to obtain stable architectures, several hierarchical TiO 2 nanostructures with {001} facets exposed have also been fabricated and show excellent performance in the Li-ion batteries.…”
Section: Introductionmentioning
confidence: 99%